Nomogram for Predicting Suboptimal Weight Loss at Three Years after Roux-en-Y Gastric Bypass Surgery in Chinese Patients with Obesity and Type 2 Diabetes - Yiming Si; Hongwei Zhang; Xiaodong Han; Weijie Liu; Yinfang Tu; Xiaojing Ma; Haoyong Yu; Yuqian Bao (Obesity Facts)
Introduction: Strategies to address suboptimal weight loss after Roux-en-Y gastric bypass (RYGB) can be developed if at-risk patients are identified in advance. This study aimed to build a pre-surgery prediction nomogram for early prediction of insufficient weight loss (IWL) or weight regain (WR) after bariatric surgery in Chinese patients. Methods: In this retrospective study, 187 patients with obesity and type 2 diabetes who underwent laparoscopic RYGB were followed yearly for 3 years. Suboptimal weight loss included IWL and WR. IWL was defined as a total weight loss percentage of <25% at 1 year postoperatively, and WR was defined as a maximum weight loss percentage of >20% at 3 years postoperatively. Multivariate logistic regression was performed to identify independent predictors and to establish a nomogram to predict the occurrence of suboptimal weight loss. Results: Multivariate logistic regression revealed that male sex (OR 4.268, 95% CI: 1.413–12.890), body mass index (OR 0.816, 95% CI: 0.705–0.946), and glycated hemoglobin (OR 1.493, 95% CI: 1.049–2.126) were independent predictors of IWL/WR. The AUC value of the nomogram constructed from the above three factors was 0.781. The Hosmer-Lemeshow test showed that the model had a good fit (p = 0.143). The calibration curve of the nomogram is close to an ideal diagonal line. Furthermore, the decision curve analysis demonstrated the good net benefits of the model. Conclusions: A nomogram based on pre-surgery factors was developed to predict postoperative IWL/WR. This provides a convenient and useful tool for predicting suboptimal weight loss before surgery.